Comparison between Bethesda and thyroid imaging reporting and data system scoring in patients of thyroid swelling at a tertiary care hospital - Ahmed, Qazi N.; Q., Sayed (International Journal of Research in Medical Sciences, 2025)
Background: Accurate diagnosis of thyroid swellings is crucial to differentiate benign from malignant lesions. The Bethesda system for reporting thyroid cytopathology (TBSRTC) and the thyroid imaging reporting and data system (TIRADS) are standardized tools used for cytological and ultrasonographic risk stratification, respectively. Objective was to compare the diagnostic performance of Bethesda and TIRADS scoring systems in evaluating thyroid nodules. Methods: A prospective observational study was conducted over 18 months at a tertiary care hospital on 150 patients with thyroid swellings. All patients underwent ultrasound-based TIRADS scoring and FNAC using the Bethesda classification. The correlation of both scores with histopathological diagnosis was analyzed. Results: Of 150 cases, 47 (31%) were malignant. TIRADS TR4-TR5 categories showed a strong correlation with Bethesda V-VI and histologically confirmed malignancies. Sensitivity, specificity, and diagnostic accuracy for TIRADS were 92.5%, 99.1%, and 97.3%, respectively. Combined TIRADS and Bethesda correlation further improved diagnostic confidence. Conclusions: TIRADS scoring showed high concordance with Bethesda categories and histopathology. Combining both systems offers a robust preoperative risk stratification tool.